2012
DOI: 10.1002/aqc.2306
|View full text |Cite
|
Sign up to set email alerts
|

Conservation status and reproduction of the critically endangered freshwater pearl mussel (Margaritifera margaritifera) in Northern Ireland

Abstract: Freshwater unionoids are one of the most threatened animal groups worldwide and the freshwater pearl mussel Margaritifera margaritifera is currently listed as critically endangered in Europe. The EC Habitats Directive requires that EU Member States monitor the distribution and abundance of this species and report regularly on its conservation status.The pearl mussel meta‐population in Northern Ireland was surveyed to assess temporal population trends in Special Areas of Conservation (SACs) and mussel reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…M. margaritifera is currently listed as critically endangered in Europe (Cuttelod et al, 2011) and protected in the European Union (EU) under annexes II and V of the European Commission Habitats Directive [92/43/EEC], which require that the EU Member States regularly assess its distribution and abundance and report its conservation status (Reid et al, 2013). In Portugal, the first comprehensive review of M. margaritifera distribution was published by Nobre (1941).…”
Section: Introductionmentioning
confidence: 99%
“…M. margaritifera is currently listed as critically endangered in Europe (Cuttelod et al, 2011) and protected in the European Union (EU) under annexes II and V of the European Commission Habitats Directive [92/43/EEC], which require that the EU Member States regularly assess its distribution and abundance and report its conservation status (Reid et al, 2013). In Portugal, the first comprehensive review of M. margaritifera distribution was published by Nobre (1941).…”
Section: Introductionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 4 Surveys of the freshwater pearl mussel in Northern Ireland indicated that the population in the Ballinderry River is still facing extinction (Beasley et al, 1998;Wilson and Roberts, 2011) as a result of multiple extensive anthropogenic impacts including land use (Reid et al, 2013) and water abstraction (NIEA, 2013a(NIEA, , 2013b. In the Ballinderry River Special Area of Conservation (SAC) M. margaritifera is in Unfavourable/Declining conservation status (Killeen, 2007;Preston, 2011).…”
Section: Page 4 Of 25mentioning
confidence: 99%
“…In the Ballinderry River Special Area of Conservation (SAC) M. margaritifera is in Unfavourable/Declining conservation status (Killeen, 2007;Preston, 2011). Although gravid mussels and infected host fish have been reported in the Ballinderry river as recently as 2011, there is no evidence of recent recruitment (Reid et al, 2013). Ballinderry Rivers Trust's Freshwater Pearl Mussel Rescue Project ('the Rescue Project') was launched in 2013; building on the success of a 15 year long captive breeding programme (Preston et al, 2007) and pilot reintroductions of juvenile mussels to the river (Wilson, 2010).…”
Section: Page 4 Of 25mentioning
confidence: 99%
See 2 more Smart Citations